A Flexible and Porous Ferrocene‐Based Gallium MOF with MIL‐53 Architecture. Issue 8 (9th February 2021) - Benecke, Jannik; Fuß, Alexander; Engesser, Tobias A.; Stock, Norbert; Reinsch, Helge
Abstract: A new gallium based metal‐organic framework, denoted as Ga‐MIL‐53‐FcDC, with the chemical formula [Ga(OH)(FeC12 H8 O4 )] was synthesized using the ferrocene containing linker molecule 1, 1'‐ferrocenedicarboxylic acid (H2 FcDC, FeC12 H10 O4 ). The porous nature of the compound could be confirmed by nitrogen sorption and a specific surface area of 270 m 2 /g was determined. The persistence of the ferrocene complex inside the structure was confirmed by Mössbauer‐, EPR and UV/VIS‐spectroscopy. Ga‐MIL‐53‐FcDC shows structural flexibility depending on which guest molecule is located in the pores of the compound. The mechanism of structural flexibility was analyzed by means of powder X‐ray diffraction adsorbing pyrazine or iodine. The flexibility of the crystal structure can be attributed to the torsion of the GaO6 octahedra in the IBU respective to each other and the torsion of the carboxylate groups of FcDC 2− relative to the aromatic ring. Abstract : As a new member of the family of MOFs with MIL‐53 topology, compound Ga‐MIL‐53‐FcDC based on ferrocenedicarboxylate is reported. Unlike its aluminum and indium based counterparts, this MOF exhibits breathing. The underlying details of the structural changes upon guest inclusion were elucidated by structure determination by powder diffraction after adsorbing iodine or pyrazine.